1996
DOI: 10.1021/ac960270t
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Oligonucleotide Mass Spectra for Determination of Sequence Using Electrospray Ionization and Tandem Mass Spectrometry

Abstract: Procedures are described for interpretation of mass spectra from collision-induced dissociation of polycharged oligonucleotides produced by electrospray ionization. The method is intended for rapid sequencing of oligonucleotides of completely unknown structure at approximately the 15-mer level and below, from DNA or RNA. Identification of sequence-relevant ions that are produced from extensive fragmentation in the quadrupole collision cell are based primarily on (1) recognition of 3'- and 5'- terminal residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
211
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 53 publications
0
211
0
Order By: Relevance
“…While McCloskey and coworkers did not observe the a n -5MeC fragment ion under CID conditions [12], the a n -5MeC fragment ion is observed for both oligonucleotides using the InHex IRMPD fragmentation scheme (Table 2). For both oligonucleotides, y n fragment ions account for 4-6% of the total fragment ions.…”
Section: Comparison Of Phosphodiester and Phosphorothioate Backbonesmentioning
confidence: 90%
See 3 more Smart Citations
“…While McCloskey and coworkers did not observe the a n -5MeC fragment ion under CID conditions [12], the a n -5MeC fragment ion is observed for both oligonucleotides using the InHex IRMPD fragmentation scheme (Table 2). For both oligonucleotides, y n fragment ions account for 4-6% of the total fragment ions.…”
Section: Comparison Of Phosphodiester and Phosphorothioate Backbonesmentioning
confidence: 90%
“…Several dissociation schemes have been used in combination with mass spectrometry to fragment DNA oligonucleotides of various lengths. These methods include nozzle-skimmer dissociation [17], collisional activated dissociation (CAD) [12,13], infrared multiple photon dissociation (IRMPD) [18], blackbody infrared radiative dissociation (BIRD) [19], and multipole storage assisted dissociation (MSAD) [20]. Several groups have shown that modified bases influence fragmentation patterns of oligonucleotides and can be used to locate modified bases that occur naturally in damaged DNA [10,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal cations are also required for the proper folding and function of many forms of RNA, including most ribozymes [7,8]. The interactions of DNA with several natural products [9] and synthetic drugs and drug candidates [10,11] are known to be metal-mediated.Mass spectrometry (MS) is well-established as a useful tool for the structural characterization and sequencing of nucleic acids [12][13][14], and has also been employed to characterize a number of nucleic acid/metal ion interactions [15]. Several previous studies have focused on the interactions of the anticancer therapeutic cisplatin or its derivatives with DNA [16 -22].…”
mentioning
confidence: 99%